Platelet-Rich Plasma-Derived Exosomes Modulate Follicular Regeneration: A Comparative Mechanistic Analysis with Minoxidil in a Preclinical Model of Androgenetic Alopecia - Trya Oktaviani; Arie Kusumawardani; Suci Widhiati; Nugrohoaji Dharmawan; Endra Yustin Ellistasari (HM Publisher, 2025)
Background: The therapeutic armamentarium for androgenetic alopecia (AGA) is limited, with variable efficacy and potential side effects associated with standard treatments like minoxidil. Platelet-rich plasma-derived exosomes (PRP-Exo) represent a novel acellular strategy, offering a concentrated payload of regenerative biomolecules. This study aimed to rigorously evaluate the therapeutic efficacy and underlying mechanisms of PRP-Exo, as a monotherapy and in combination with minoxidil, in a validated murine model of AGA. Methods: A parallel-group, randomized, double-blind, controlled experimental study was conducted. Thirty-two male C57BL/6 mice with testosterone-induced AGA were randomized (n=8/group) to one of four groups: Negative Control (NC), Positive Control (PC; 5% topical minoxidil), Treatment 1 (T1; intradermal PRP-Exo), or Treatment 2 (T2; combination of PRP-Exo and minoxidil). PRP-Exo were characterized by Transmission Electron Microscopy, Nanoparticle Tracking Analysis, and ELISA for marker proteins. After a 14-day treatment period, efficacy was assessed via hair follicle density (HFD), anagen-to-telogen (A/T) ratio, and hair shaft thickness. Mechanistic insight was obtained by quantifying tissue protein levels of Ki-67 and β-catenin by ELISA. Results: All active treatments significantly improved hair regeneration compared to the NC group. The combination therapy (T2) demonstrated the most profound effects across all metrics, showing statistically superior outcomes compared to both minoxidil (PC) and PRP-Exo (T1) monotherapies in HFD (65.8 ± 12.1 vs. 36.2 ± 8.5 and 47.3 ± 10.4 follicles/mm², respectively; p<0.01). Furthermore, T2 treatment led to the highest A/T ratio and hair shaft thickness. ELISA revealed that T2 treatment also resulted in the highest tissue concentrations of the proliferation marker Ki-67 and the Wnt pathway protein β-catenin, suggesting enhanced mitogenic activity and modulation of key developmental pathways. Conclusion: PRP-Exo is a potent hair regenerative agent, significantly outperforming minoxidil in this preclinical model. The combination of PRP-Exo and minoxidil exhibits a synergistic effect, promoting superior follicular regeneration by concurrently stimulating tissue proliferation and upregulating key components of the anagen-promoting Wnt signaling pathway. These findings underscore the significant clinical potential of PRP-Exo as a next-generation therapy for AGA.